TINJAUAN HUKUM KEDUDUKAN AKTA HIBAH WASIAT YANG MELAMPAUI BAGIAN MUTLAK AHLI WARIS LEGITIMARIS: LEGAL REVIEW OF THE POSITION OF THE WISDOM OF WISDOM THAT EXCEEDS THE ABSOLUTE SECTION OF LEGITIMARY HERITAGES - Imam, Imam; Kamsilaniah; Tira, Andi (Clavia, 2022)
This study aims to determine and analyze the position of the will of the heirs to the absolute part of the heirs. The research method used is qualitative legal research. The types and sources of data consist of primary data in the form of laws and regulations, and Court Decisions as well as secondary legal materials consisting of books, articles and journals related to this research. The entire legal material is collected in a structured systematic manner using qualitative measures and presented in a descriptive analysis. The results of the study indicate that a will or testamental grant that violates the "legitieme portie" is considered "null and void" by itself andais considered to have noibinding force fromithe start. However, inipractice, a testament deed / will grant isivalid even if it containsia violation of the heir's legitimacy portie, ias long as it has not been canceled by the injured heir, so that its nature is no longer "null and void" but becomes "cancellable" and There are 2 (two) types of legal consequences related to a grant or testamentary grant that violate the absolute or legitime portie depending on the legitimate action. If the legiti- mate does not object, then the act of grant or testamentary grant that violates the absolute or legitime part of the portie is considered valid and enforceable if the legiti- mate demands his rights, then the provision in the grant or testamentary grant that violates the absolute part or legitime portie cannot be carried out and refers to Article 920 of the Civil Code, thus the deed remains valid as long as it is not contested by the heirs.